Time War: Paul Virilio and the Potential Educational Impacts of Real-Time Strategy Videogames - Waddington, David (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2020)
This essay explores the possibility that a particular type of video game—real-time strategy games—could have worrisome educational impacts. In order to make this case, I will develop a theoretical framework originally advanced by French social critic Paul Virilio. In two key texts, Speed and Politics (1977) and “The Aesthetics of Disappearance” (1984), Virilio maintains that society is becoming “dromocratic” – determined by and obsessed with speed. Extending Virilio’s analysis, I will argue that the frenetic, ruthless environment of real-time strategy games may promote an accelerated, hypermodern way of thinking about the world that focuses unduly on efficiency.